2002
DOI: 10.1021/bc020025i
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Congeners of Tyrosine-Based P2X7 Receptor Antagonists:  Probing Multiple Sites for Linking and Dimerization

Abstract: Chemically funtionalized analogues of antagonists of the P2X 7 receptor, an ATP-gated cation channel, were synthesized as tools for biophysical studies of the receptor. These functionalized congeners were intended for use in chemical conjugation with retention of biological potency. The antagonists were L-tyrosine derivatives, related to [N-benzyloxycarbonyl-O-(4-arylsulfonyl)-Ltyrosyl]benzoylpiperazine (such as MRS2409, 2). The analogues were demonstrated to be antagonists in an assay of human P2X 7 receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
(109 reference statements)
0
13
0
Order By: Relevance
“…tyrosine), 2) R 2 (the tyrosine side chain), and 3) R 3 (the substituent attached to the N-piperazine) (Fig. 15) [137][138][139].…”
Section: Calmidazoliummentioning
confidence: 99%
See 1 more Smart Citation
“…tyrosine), 2) R 2 (the tyrosine side chain), and 3) R 3 (the substituent attached to the N-piperazine) (Fig. 15) [137][138][139].…”
Section: Calmidazoliummentioning
confidence: 99%
“…15 ) on the P2X 7 R antagonistic properties was compared on the basis of inhibition of K + release [137,138]. At the R 1 position, large hydrophobic moieties linked to the amino position through sulfonamide (34a-b) or carbamate (34c) groups were preferable for P2X 7 R inhibition.…”
Section: Calmidazoliummentioning
confidence: 99%
“…The selective P2X 2,3 /P2X 3 receptor antagonist A-317491 has antinociceptive properties and has been developed as a radioligand, but suffers from low bioavailability . Derivatives of the isoquino-line KN-62, such as MRS2427 (Chen et al 2002) and a high affinity radioligand (Romagnoli et al 2004), and novel 4,5-diarylimidazolines and other antagonists identified through screening of chemical libraries are selective for the P2X 7 receptor (Merriman et al 2003, Baxter et al 2003.…”
Section: Novel Non-nucleotide Antagonist Of P2 Receptorsmentioning
confidence: 99%
“…KN-62 antagonizes the human P2X 7 receptor more potently than mouse or rat homologues. The tyrosine derivative MRS 2409 30a (IC 50 of 200 nM at hP2X 7 ) and its derivatives [25] act as potent antagonists of both mouse and human P2X 7 receptors. A functionalized congener approach to the design of P2X 7 receptor antagonists [25] has resulted in the amine-functionalized antagonist MRS 2483 30b.…”
Section: Antagonistsmentioning
confidence: 99%
“…The tyrosine derivative MRS 2409 30a (IC 50 of 200 nM at hP2X 7 ) and its derivatives [25] act as potent antagonists of both mouse and human P2X 7 receptors. A functionalized congener approach to the design of P2X 7 receptor antagonists [25] has resulted in the amine-functionalized antagonist MRS 2483 30b. Baraldi and coworkers have explored the SAR in this series of P2X 7 receptor antagonists, identifying 31 as a particularly potent congener with an IC 50 value of 1.3 nM at hP2X 7 receptors [26].…”
Section: Antagonistsmentioning
confidence: 99%